Kultúra és fejlődés Afrikában - Kovács, Máté (Afrika Tanulmányok / Hungarian Journal of African Studies, 2008)
On the level of principles it is widely recognized in international and African standard-setting instruments that culture has a central role as a framework, a resource and priority objective of human development. However, development programmes in Africa often ignore the cultural specificities of the populations, which then causes the failure of many initiatives. There is a need to integrate a cultural and participatory approach in development planning processes via the greater involvement of societies at large, as well as for social scientists and cultural specialists to the definition and implementation of development programmes and projects. Culture can also contribute to Africa’s economic development, as a productive sector based on the assets of African cultural heritage and creativity through generating income and creating jobs. African governments and their international partners should take urgent measures for creating an enabling environment for the development of African creative economy.